Current research in management - Hammond, Valerie (London ; Dover, N.H. : F. Pinter for the Association of Teachers of Management, 1985)
The book is divided into five major themes. Several of the papers draw on international work and offer comparative studies which reflect the multi-cultural arena in which many managers operate today.
Includes bibliographical references.
hza 28/08/2018
Loans
Keywords: Management